An assessment of surface water quality and heavy metals involving the rare earth elements in Sungai Tunggak and Sungai Balok, Gebeng, Kuantan, Pahang - Ab Wahab, Siti Umikalthum; Shaibullah, Siti Hajar; Abu Samah, Mohd Armi; Mohd. Aris, Mohd Shukri (Penerbit Universiti Malaysia Pahang, 2016)
Water pollution caused by rare earth elements (REEs) and heavy metals have become serious threats to the survival of aquatic organisms, human, and environment especially in Pahang. This alarming circumstance has inspired the study to measure water quality parameters and concentration of REEs and heavy metals in the rivers within an industrial area. For achieving these objectives, collected data was done in dry seasons (April – June) in year 2014 and 2015. Both data were compared and analyzed based on different locations at the selected river in Gebeng industrial area, Pahang. The physical parameters such as temperature, specific conductivity, pH, turbidity, dissolved oxygen (DO), and biological oxygen demand (BOD) were measured by using hydrolab. The water samples were then collected for tracing the REEs and heavy metals by using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). Malaysian Interim National Water Quality Standard (INWQS) was used as reference. Water quality parameters were all within the permissible limit except for turbidity in both year 2014 and 2015. Besides, REEs elements investigated in this study showed that the concentration of one of the investigated elements was thorium exceeded the permissible limit at the upstream area which recorded 2.54 ppb in year 2014. The current study progress is not fully investigated, but as the whole, the study outcomes envisaged the pollutants presence may be reflected with river water flow from upstream, middle stream and downstream.